Human red cell adenylate kinase polymorphism in West Malaysian populations - Chan, K.L. (Karger Publishers, 1971)
Human red cell adenylate kinase polymorphism was studied in the Malays, Chinese and Indians of West Malaysia. The AK2 allele was found to be absent in Chinese while its frequency is relatively high in Indians (0.1101) and low but polymorphic in Malays (0.0187). The frequencies and distribution of the AK phenotypes among the three ethnic groups are significantly different to differentiate the Malays, Chinese and Indians of West Malaysia as distinct populations. © 1971 S. Karger AG, Basel.